Geoplastics and its Significance in Landscape Design - D., Adilova; N., Mukhamadieva (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the issues of geo plastics, their types, plastic features, methods of application in landscape design compositions.